SARS-CoV-2 coinfection with additional respiratory virus does not predict severe disease: a retrospective cohort study. (23rd September 2021) - Chekuri, Sweta; Szymczak, Wendy A; Goldstein, D Yitzchak; Nori, Priya; Marrero Rolon, Rebecca; Spund, Brian; Singh-Tan, Sumeet; Mohrmann, Laurel; Assa, Andrei; Southern, William N; Baron, Sarah W
Abstract: Background: The coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) claimed over 4 million lives by July 2021 and continues to pose a serious public health threat. Objectives: Our retrospective study utilized respiratory pathogen panel (RPP) results in patients with SARS-CoV-2 to determine if coinfection (i.e. SARS-CoV-2 positivity with an additional respiratory virus) was associated with more severe presentation and outcomes. Methods: All patients with negative influenza/respiratory syncytial virus testing who underwent RPP testing within 7 days of a positive SARS-CoV-2 test at a large, academic medical centre in New York were examined. Patients positive for SARS-CoV-2 with a negative RPP were compared with patients positive for SARS-CoV-2 and positive for a virus by RPP in terms of biomarkers, oxygen requirements and severe COVID-19 outcome, as defined by mechanical ventilation or death within 30 days. Results: Of the 306 SARS-CoV-2-positive patients with RPP testing, 14 (4.6%) were positive for a non-influenza virus (coinfected). Compared with the coinfected group, patients positive for SARS-CoV-2 with a negative RPP had higher inflammatory markers and were significantly more likely to be admitted ( P =  0.01). Severe COVID-19 outcome occurred in 111 (36.3%) patients in the SARS-CoV-2-only group and 3 (21.4%) patients in the coinfected group ( P =  0.24). Conclusions: Patients infected with SARS-CoV-2 along with a non-influenza respiratory virus had less severe disease on presentation and were more likely to be admitted—but did not have more severe outcomes—than those infected with SARS-CoV-2 alone.